Energy Resonances for $^1P^o,$ $^1D^e,$ $^1F^o,$ $^1G^e,$ and $^1H^o$ Autoionizing States of the Helium Isoelectronic Series Below the $n=2-4$ Hydrogenic Thresholds (Journal of Atomic and Molecular Sciences, 2018)
General formalism of special form of Hylleraas correlated wave functions (SFHCWF) is demonstrated in this paper. The adequacy of the SFHCWF in the description as well as of the singlet than of the triplet excited states of two electron systems is also presented in this work. Application of SFHCWF to the calculations of doubly excited nlnl' states (n=2-4) in the helium-like ions is done, using the screening constant by unit nuclear charge method in the framework of a variational procedure. Comparison with various available theoretical and experimental literature values indicates a good agreement.